Detox Fashion Sustainable Chemistry and Wet Processing - Muthu, Subramanian Senthilkannan (Textile Science and Clothing Technology,, 2018)
This second volume on detox fashion covers five key aspects relevant to the topic sustainable chemistry and wet processes: Sustainable Chemicals: A Model for Practical Substitution; Sustainable Wet Processing; Coloration and Functional Finishing of Cotton with Plant Extracts; Call for an Environmental Impact Assessment of Bio-based Dyeing-an Overview; and Enzymes: Biocatalysts for Cleaning Up the Textile and Apparel Sector. The book also presents interesting solutions at the level of the supply chain with regard to sustainable chemistry and wet processes.